Предмет: Математика,
автор: sergejcevvasilij
Помогите пожалуйста,,,,,,,,,,,.....
Приложения:
Ответы
Автор ответа:
1
Ответ:
-y(29y+10)
Пошаговое объяснение:
= -y(4(7y+4)-(-y+6))=
=-y(28y+16+y-6)=
=-y(29y+10)
Автор ответа:
0
если упростить то тогда
-2у(14у-10) будеть
-28y²-16y+6y=0
-28y²-10y=0
-2y(14y+5y)=0
-2y=0
y=0/-2=-0
14y+5y=0
19y=0
y=0
Похожие вопросы
Предмет: Математика,
автор: Ксюша24Качалова
Предмет: Математика,
автор: hhhu375
Предмет: Русский язык,
автор: Dasha34342
Предмет: Математика,
автор: belkaxd05
Предмет: Алгебра,
автор: igorf5